2008
DOI: 10.1590/s0100-204x2008001000005
|View full text |Cite
|
Sign up to set email alerts
|

Extrato de casca de café, óleo essencial de tomilho e acibenzolar-S-metil no manejo da cercosporiose-do-cafeeiro

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito de concentrações de extrato de casca de café, óleo essencial de tomilho e acibenzolar-S-metil na germinação, no crescimento micelial e no desenvolvimento in vivo de Cercospora coffeicola, além de caracterizar a efi ciência deles como indutores de resistência, e determinar a atividade da enzima peroxidase e o acúmulo de lignina nos tecidos de cafeeiro. O extrato de casca de café não afetou a germinação, entretanto, inibiu o crescimento micelial proporcional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 18 publications
2
15
0
10
Order By: Relevance
“…Similarly, Pereira et al (2008) observed reduction of Coffea coffeicola conidial germination when subjected to increasing concentrations of the essential oil of thyme. This effect is probably due to the presence of compounds such as thymol and carvacrol, already known for their fungicidal and bactericidal properties (ZAMBONELLI et al, 2004).…”
Section: Resultsmentioning
confidence: 71%
“…Similarly, Pereira et al (2008) observed reduction of Coffea coffeicola conidial germination when subjected to increasing concentrations of the essential oil of thyme. This effect is probably due to the presence of compounds such as thymol and carvacrol, already known for their fungicidal and bactericidal properties (ZAMBONELLI et al, 2004).…”
Section: Resultsmentioning
confidence: 71%
“…However, a significant increase in levels of soluble lignin was observed in coffee plants treated with citronella essential oil. Pereira et al, (2008) found increased activity of peroxidases in coffee plants sprayed with thyme essential oil and challenged with C. coffeicola seven and eleven days after application. Also, some similar results have been shown in other pathosystems.…”
Section: Resultsmentioning
confidence: 86%
“…Recently, some of these effects, such as cellular disorganization and vacuolization, were observed in urediniospores of H. vastatrix (PEREIRA et al, 2012) and conidia of C. coffeicola (PEREIRA et al, 2008) exposed to citronella essential oil. Billerbeck et al, (2001) and Helal et al, (2007) also reported that the hyphae walls of Aspergillus niger Van Tieghem and A Aspergillus flavus Link, respectively, disappeared in some regions after treatment with citronella essential oil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A concentração 50 µg mL -1 de ASM aumentou significativamente a germinação dos conídios in vitro. Pereira et al (2008) O aumento no número de lesões de cercosporiose em cafeeiros previamente tratados com 120 µg mL -1 de harpina, em relação ao controle (Tabela 2), pode estar associado ao estímulo na germinação dos conídios do patógeno na presença da proteína (Tabela 4).…”
Section: Resultsunclassified